Ilmu dan Sarjana Menurut Al-Nadwi: Suatu Review dan Teks - Wan Abdullah, Wan Suhaimi (Jurnal Usuluddin, 2000)
Al-Nadwi in his speech entitled "The Place of Knowledge and Responsibilities of Those Who Acquire It" describes the concept of knowledge and the responsibilities of scholars in Islam. It tries to prove how the Islamic concept of knowledge and scholarship is important for the development of the human thought and modern sciences, especially in the modern world. This article is a translation of this speech preceded by a brief review on it.